Implementasi Kebijakan Ruang Terbuka Hijau Kota Malang (Studi pada Kawasan Stadion Gajayana Malang). - Deta Ratmalia Lestari (Jurnal Administrasi Publik, 2016)
Abstract: The Implementation of Green Open Space Policy in Malang City (Studies in area Stadion Gajayana Malang). Olympic Garden Mall construction built on region Gajayana Stadium, is an example of green space that has been experienced over the function. In fact in an effort to control utilization and green open spaces that still menglami diverse persolaan, this needs to be thought was lack of firmness in implementing policies related to green space based on the applicable law and pay attention to the implementation of the policy guidelines for the management of spatial planning at the regional Regulation No.4 of 2011, on Spatial Planning Malang 2010-2030. Implementation of green open space in Malang implemented by the Department of Hygiene and Malang (DKP), the planning done by DKP and BAPPEDA with the actors involved are actors inside govermnet and actors outside government, including actors inside government are the actors in governance namely the central government and municipal authorities, in this case the municipality is DKP and BAPPEDA. As well as actors outside government are non-state actors such as private parties (CSR) and community. RTH policy implementation process Malang antaralain includes three stages, among others, is the stage of combining the plan, the implementation phase of the program and determine the stage of monitoring schedule. There are factors supporting and inhibiting factors, in the process of implementing that one of them is supporting the implementation of policies RTH Malang terjalinya cooperation between the private sector and the inhibiting factors are land yangdari year to year has decreased the amount. Keywords : implementasi kebijakan, ruang terbuka hijau, kota malang Abstrak: Implementasi Kebijakan Ruang Terbuka Hijau di Kota Malang (Studi pada Kawasan Stadion Gajayana Malang). Pembangunan Mall Olimpic Garden yang dibangun diatas kawasan Stadion Gajayana, adalah contoh RTH yang telah mengalami alih fungsi. Pada kenyataanya dalam upaya pemanfaatan dan pengendalian ruang terbuka hijau yang masih menglami beragam persolaan, hal ini perlu dikiranya adanya ketegasan dalam Â melaksanakan kebijakan terkait RTH berdasarkan Undang-undang yang berlaku dan memperhatikan pedoman pelaksanaan kebijakan pengelolaan penataan ruang pada Peraturan Daerah No.4 Tahun 2011, tentang Rencana Tata Ruang Wilayah Kota Malang 2010-2030. Perencanaan yang dilakukan oleh DKP serta BAPPEDA dengan aktor yang terlibat diantaranya adalah aktor inside govermnet dan aktor outside government. Serta aktor outside government adalah aktor non-pemerintah seperti pihak swasta (CSR) dan masyarakat. Proses implementasi kebijakan RTH Kota Malang antaralain meliputi tiga tahap, antara lain adalah tahap menggabungkan rencana, tahap pelaksanaan program dan tahap menentukan jadwal pengawasan. Terdapat faktor pendukung dan faktor penghambat, didalam proses implementasi yaitu salah satunya adalah yang mendukung implementasi kebijakan RTH Kota Malang terjalinya kerjasama antara pihak swasta dan faktor penghambat adalah lahan yangdari tahun ke tahun mengalami penurunan jumlah. Â  Kata kunci: implementasi Kebijakan, Ruang Terbuka Hijau, Kota Malang